FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN NON KEUANGAN YANG TERDAFTAR DI BEI - KEZIA CRUSITA NOVIANA; NELLIYANA NELLIYANA (Jurnal Bisnis dan Akuntansi, 2017)
The purpose of this research is to obtain an empirical evidence about influence of variables on firm value. These variables are supply chain auditor, firm growth, firm size, leverage, investment, firm age, free cash flow, board size, profitability. The population used in this study are non financial companies listed in Indonesia Stock Exchange during 2013 until 2015. The sampling method used is purposive sampling and to test the hypothesis using multiple regression method. The result of this research indicate that leverage, firm age, and profitability have influence on firm value. However, supply chain auditor, firm growth, firm size, investment, free cash flow and board size have no influence on firm value.